Pengolahan Ikan Berbasis Bahan Lokal untuk Makanan Tambahan Pencegah Stunting - Yuniati, Dewi; Ayu Indayanti Ismail; Novi Aryanti (Jurnal Galung Tropika, 2024)
Diversity of complementary food intake for children aged 6-24 months is crucial to reducing new stunting rates. The combination of the three ingredients, flying fish, millet flour, and moringa leaves, is expected to be a PMT (Supplementary Food Provision) menu to fulfill nutrition for children aged 6-24 months and prevent stunting. The study aimed to analyze the level of preference and quality of the functional food formula for nuggets through organoleptic tests and nutrient content in nuggets. This study was conducted in July - August 2024. In this study, nugget formulations, organoleptic tests, and analysis of nutrient content in nuggets were carried out. The results of the organoleptic test of the level of preference for nuggets obtained an average value of 3.67 for color and aroma, 3.43 for taste, and 3.5 for texture. The results of the proximate test showed that nuggets contain complete nutrients. Nuggets contain 20.41% protein, 0.47% fat, 2.56% ash content, 25.59% carbohydrate, 50.71% water content, 29.045 mg/kg iron (Fe), 21.01 mg/kg zinc (Zn), and 120.21 mg/kg calcium (Ca). Overall, the assessment of the level of preference for nuggets made from flying fish, millet flour, and moringa leaves is above 3, which means that the nugget product is acceptable to the panelists. Nuggets contain complete nutrition, a reasonably high protein content, and essential minerals needed to reduce the risk of stunting.